Equality in the Miyaoka–Yau inequality and uniformization of non-positively curved klt pairs - Claudon, Benoît; Graf, Patrick; Guenancia, Henri (Comptes Rendus. Mathématique)
Let $(X, Δ )$ be a compact Kähler klt pair, where $K_X + Δ $ is ample or numerically trivial, and $Δ $ has standard coefficients. We show that if equality holds in the orbifold Miyaoka–Yau inequality for $(X, Δ )$, then its orbifold universal cover is either the unit ball (ample case) or the affine space (numerically trivial case).